Pengaruh Tata Kelola Perusahaan Terhadap Profitabilitas Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Fariz Satriadi; Masyhuril Amri Bagaskara; Titin Pranoto; Luciana Haryono (Studi Akuntansi dan Keuangan Indonesia, 2018)
This research is aimed to analyze the influence of good corporate governance to company’s profitability. This research is based on the previous research that is done by Zabri, Ahmad and Wah (2016). Aside from board size and independent commissioner’s composition, this research added few variables which are; board meeting, audit committee size and audit committee meeting with firm age and leverage as the control variables. Profitability is measured by return on asset (ROA) and return on equity (ROE). Samples of this study consist of 170 non-financial listed firms from 2012 – 2016. Multiple regressions were used to test the hypotheses. The result of this research has shown that good corporate governance gives a significant influence on the profitability of the companies located in Indonesia. Keywords: Firm age, good corporate governance, leverage, and profitability https://doi.org/10.21632/saki.1.2.134-157